Perceived Value Factor Influences on the satisfaction of using the YelloTalk application service of Generation Z - Saetan, Kitsanapol; Putthajaksri, Thanached; Haphayong, Peechaya; Pongsai, Witthawat; Tangpattanakit, Jaruporn (NIDA Business Journal, 2024)
The YelloTalk application is highly popular among the Generation Z demographic, owing to the rapid advancements in technology, which present an opportunity for its growth. This research aims to study the factors influencing perceived value, which in turn affects satisfaction in using the YelloTalk application among Generation Z users. Data was collected through online questionnaires from a sample group of 350 individuals. The data was analyzed, and hypotheses were tested using multiple regression analysis. The research findings indicate that factors such as social self-image expression, social relationship support, perceived enjoyment, perceived cost of service, application competency, and functional quality significantly influence satisfaction in using the YelloTalk application. However, The aesthetics variable does not influence satisfaction with using the YelloTalk application. This research is beneficial for the application industry to apply in strategic planning or business development, aiming to meet consumer needs effectively and enhance consumer satisfaction in the application industry.